Epicardial fat thickness is associated with aortic intima‐media thickness in patients without clinical manifestation of atherosclerotic cardiovascular disease. Issue 8 (3rd July 2017) - Acele, Armağan; Baykan, Ahmet O.; Yüksel Kalkan, Gülhan; Çeliker, Emel; Gür, Mustafa
Abstract : Background: Although the relationship between epicardial fat thickness (EFTh) and coronary atherosclerosis is well established, this relation in the early periods of atherosclerosis has not been fully demonstrated. On the other hand, thoracic aortic intima‐media thickness (IMT) rather than carotid IMT was reported as an earlier marker of preclinical atherosclerosis. Objective: We aimed to assess the relationship between thoracic aortic IMT and EFTh in patients undergoing transesophageal echocardiography (TEE) examination for different indications. Methods: We included 104 patients (mean age 38±11.4 years), who underwent TEE for various indications. The patients were divided into two groups according to the median thoracic aortic IMT values (IMT normal group<10 mm and IMT abnormal group≥10 mm). EFTh was obtained using two‐dimensional transthoracic echocardiography on the right ventricular free wall during systole and diastole. Results: The highest EFTh values (3.3±0.96 mm vs. 4.51±0.66 mm, P <.001) were observed in the abnormal aortic IMT group. Multivariate linear regression analysis showed that aortic IMT was independently correlate with EFTh (β=0.423, P <.001). Moreover, EFTh was found to be associated with history of transient ischemic attack ( r =.403, P <.001) and abnormal IMT ( r =.643, P <.001) in bivariate analysis. Conclusion: Epicardial fat thickness is independently related to the extent of subclinical thoracic aortic atherosclerosis. Increase in EFTh may be crucial marker for initial atherosclerosis.